Semantic Documentation in Project Management - Bastos, Erick Casagrande; Barcellos, Monalessa Perini; Falbo, Ricardo de Almeida (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2016: Anais do XV Simpósio Brasileiro de Qualidade de SoftwareDO - 10.5753/sbqs.2016.15152, 2016)
The existence of project management supporting tools did not eliminate the need of using desktop documents in this domain. However, retrieving information from documents is usually not trivial and depends on human effort. In this work we propose the use of semantic documentation in the project management domain as a way of getting useful information from data recorded in documents and spreadsheets. For this, we developed the Software Project Management Ontology and explored it to create features to support activities related to scope, time and cost management. The features were implemented in a specialization of the Infrastructure for Managing Semantic Documents, which was evaluated through an experimental study.